Development of ATOBAT: an Android-BasedMedicinal Plant Application Using Google Sites andMIT App Inventor - Zalfa Nur Awali; Sugeng Supriyanto; Anwar Sodik; Muhammad Husnul Khuluq; Herniyatun (JUITA: Jurnal Informatika, 2025)
Indonesia, as a "Live Laboratory," has abundant biological wealth, especially in traditional medicinal plants. The knowledge of these plants has been passed down through generations within communities. However, modernization and societal shifts have contributed to a decline in public understanding of the benefits of medicinal plants. In Pagebangan Village, while 55 types of medicinal plants are recognized, many inhabitants lack detailed knowledge about the specific advantages of each plant. To address this critical knowledge gap, an Android application named ATOBAT was developed. This application was created using Google Sites and MIT App Inventor, both of which do not require advanced programming skills. The primary aim of ATOBAT is to enhance residents' understanding of the medicinal plants available in their environment. This research employs an experimental design utilizing the Research and Development (R&D) methodology, which encompasses the design, development, and evaluation of the application. The evaluation process included validation by media experts and feasibility testing with 92 respondents from the Pagebangan Village community, using purposive sampling and a Likert scale questionnaire. The results indicated a feasibility score of 74% from media experts and 85% from users, confirming that the ATOBAT application effectively enhances community understanding of medicinal plants and their benefits.